The Abundance of Harmful Rare Homozygous Variants in Children of Consanguineous Parents - Sankar Subramanian (Biology)
The children born of consanguineous union were found to have a higher incidence of recessive genetic diseases than the offspring of unrelated parents. The reason for this was predicted to be the presence of more deleterious rare homozygous genetic variants in the former compared to the latter. However, the magnitude of this difference is unknown. Using more than 2500 whole genomes, we show here that the individuals born of the union between double (paternal and maternal) first cousins had 20 times more deleterious rare homozygous single nucleotide variants (SNVs) than those who had unrelated parents. Furthermore, the children of first cousins had 10 times, and the children of second cousins had two times more of these SNVs compared to those present in the offspring of unrelated parents. Similar magnitudes of differences were found for the nonsynonymous deleterious rare homozygous SNVs (19, 10, and 2 times, respectively). In contrast, the differences in the number of deleterious low-frequency and common homozygous variants between the children of cousins and those of unrelated parents were 1–3 times and 1–7%, respectively. These results suggest that the offspring of consanguineous union could have a 20 times higher risk of recessive autosomal diseases caused by rare variants. Conversely, consanguinity appears to have little effect on the risk of common diseases. These findings have implications for future clinical research in identifying genetic variants associated with inherited diseases. Furthermore, the magnitude of the elevated risk revealed in this study could be useful in genetic counseling and for public health in creating awareness.